Disinfection of biological agents in the field using a mobile advanced oxidation process - Mudd, Shannon Marie (Kansas State University, 2018)
As an alternative to traditional disinfection methods, the use of an advanced oxidation process (AOP) was investigated for exercise in theatre to expediate water usability. The system utilized for this study was a mobile combination of UV irradiation and ozonation, which provided multiple mechanisms for treatment without the addition of chemicals. As a compact and transportable apparatus, the proposed unit would treat water for secondary purposes including vehicle washing, equipment cleaning, and other demands not involving consumption or personal hygiene. Several varying dilutions of hog farm lagoon water and military vehicle wash water were combined with microbial concentrations up to 9.10E+04 mpn/mL. The inoculant tested was Escherichia coli for frequency of occurrence and similarities to microbes of bioterrorism. The overall results for the AOP treatment do not indicate a connection between inactivation and suspended solids, but there does exist a significant relationship to contact time as indicated by changes in the flow rate. The experimental data showed a correlation to increased inactivation with lower flow rates. Although inactivation was not complete, the once through flow system could be adjusted to recirculate water for additional treatment. Due to time constraints additional testing was not possible, but the benefit could be examined in future research. The relationship of TSS to inactivation was not evident as inactivation occurred in similar distributions whether suspended solids were elevated or reduced.
Keywords: AOP; Advanced oxidation; Ozone; Irradiation; UV; Escherichia; E. coli